222 Prognostic value of high-sensitivity cardiac troponin I early after coronary artery bypass graft surgery. (8th December 2021) - Nanni, Samuele; Corsini, Anna; Garofalo, Mattia; Schinzari, Matteo; Nardi, Elena; Semprini, Franco; Baiocchi, Massimo; Castelli, Andrea; Pacini, Davide; Galie, Nazzareno
Abstract: Aims: The diagnosis of periprocedural myocardial infarction (PMI) after coronary artery bypass graft (CABG) is based on biochemical markers along with clinical and/or instrumental findings. However, there is not a clear cut-off value of high-sensitivity cardiac troponin (hs-cTn) to identify PMI. We hypothesized that isolated hs-cTn concentrations in the first 24 h following CABG could predict cardiac adverse events (in-hospital death and PMI) and/or left ventricular ejection fraction (LVEF) decrease. Methods and results: We retrospectively enrolled all consecutive adult patients undergoing CABG at our Institution over 1 year. Hs-cTnI concentrations (Access assay, Beckman-Coulter) were serially measured in the post-operative period and correlated with post-operative outcomes. 300 patients were enrolled; 71.3% of them underwent CABG alone, mainly on-pump (96.7%), 33.7% in the setting of an acute coronary syndrome. Most patients showed hs-cTnI values superior to the limit required by the latest guidelines for the diagnosis of PMI. Five patients (1.7%) died, 8% developed a PMI, and 10.6% showed a LVEF decrease ≥10%. Hs-cTnI concentrations did not correlate with death or PMI whereas they did correlate with LVEF decrease ≥ 10% ( P -value < 0.05 at any time interval). Indeed, higher hs-cTnI values at 9–12 h post-operatively, along with previous cardiac surgery, number of surgical procedures, longer cardiopulmonary bypass time, and PMI diagnosis were predictors of LVEF decrease. Conclusions: After CABG surgery, hs-cTnI at 9–12 h post-operatively may be a useful method to early identify patients at risk for LVEF decrease and to guide early investigation and management of possible post-operative complications.